Action of two macrophytes for the treatment of wastewater from the stabilization lagoons of Magollo, Tacna - Peru - Limache Quispe, Fernando Daniel (2022)
Magollo's stabilization ponds have been on the verge of collapse on several occasions, resulting in inefficient pollutant removal. The present investigation sought to perform a comparative evaluation of water hyacinth (Eichhornia Crassipes) and water lettuce (Pistia Stratiotes) for the treatment of wastewater from the stabilization ponds of Magollo, Tacna - Peru. For this, 6 polypropylene containers were used (3 to position Eichhornia Crassipes and 3, for Pistia stratiotes), depositing 20 liters of residual water collected from the Magollo lagoons in each one (all being fed by oxygenation engines of 2,5 Wts). The analyzes were carried out following the stipulations of the “Standard Methods for the examination of Water and Wastewater” in the facilities of the Analytical Laboratory E.I.R.L at 0, 20, 40 and 60 days of hydraulic retention. It was determined that Eichhornia crassipes is more efficient than Pistia stratiotes in the removal of the parameters: fecal coliforms, total coliforms, electrical conductivity and BOD5, however, the water lettuce was able to stabilize the pH, increase the dissolved oxygen and reduce the COD in a higher proportion than water hyacinth. It was concluded that both species are efficient in removing pollutants from wastewater, being able to adapt perfectly to the weather conditions of the city of Tacna.